THE INFLUENCE OF LOCATION, PRODUCT QUALITY, AND SERVICE QUALITY ON CUSTOMER LOYALTY WITH PURCHASE INTENTION AS INTERVENING VARIABLE - Ariyanti, Kristi; Fachrodji, Achmad (Dinasti International Journal of Digital Business Management, 2021)
This study was written with the aim of examining the impact of location, product quality and service quality on consumer loyalty mediated by buying interest. The population analyzed is membership consumers who are Golf Restaurant Pangkalan Jati Depok and have visited at least 3 times. Calculation of the sample using the Hair’s formula which explains that the sample is calculated based on the number of indicators multiplied by 5, so that 180 respondents are obtained. Structural Equation Model was chosen as the method of analysis using PLS software. The results show that product quality and service quality have a positive impact on buying interest and consumer loyalty. Location is not able to have an impact on Buying Interest and Consumer Loyalty. Purchase intention is not able to mediate Location to Consumer Loyalty. Meanwhile, Purchase Interest is able to mediate the effect of Product Quality and Service Quality on Customer Loyalty with the Partial Mediation category.